2021
DOI: 10.1101/2021.06.18.449036
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Communication between the mediodorsal thalamus and prelimbic cortex regulates timing performance in rats

Abstract: Predicting when future events will occur and adjusting behavior accordingly is critical to adaptive behavior. Despite this, little is known about the brain networks that encode time and how this ultimately impacts decision-making. One established finding is that the prefrontal cortex (PFC) and its non-human analogues (e.g., the rodent prelimbic cortex; PL) mediate timing. This provides a starting point for exploring the networks that support temporal processing by identifying areas that interact with the PFC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…We also analyzed single-trial patterns of responding, again using 1s bins. Specifically, we identified bursts of responses using a standard approach in which a dual step-function (i.e., rectangular pulse: first step-up, second step-down) is fit to response rates across time during a given trial (Church et al, 1994;De Corte et al, 2021). The algorithm iteratively fits the step function across time, finding the points where absolute residuals are minimized.…”
Section: Methodsmentioning
confidence: 99%
“…We also analyzed single-trial patterns of responding, again using 1s bins. Specifically, we identified bursts of responses using a standard approach in which a dual step-function (i.e., rectangular pulse: first step-up, second step-down) is fit to response rates across time during a given trial (Church et al, 1994;De Corte et al, 2021). The algorithm iteratively fits the step function across time, finding the points where absolute residuals are minimized.…”
Section: Methodsmentioning
confidence: 99%
“…As effects such as temporal averaging, Vierordt’s law, and covariance expectations often operate cross-modally, one might expect a multisensory area to be involved. Functionally, the MD plays a broad role in cognition (Markowitsch, 1982 ; Peräkylä et al, 2017 ), and while data are limited, manipulations of the MD disrupt baseline timing performance (Yu et al, 2010 ; Lusk et al, 2020 ; De Corte et al, 2021 ). As a notable example, Lusk et al ( 2020 ) recently inhibited the MD optogenetically during the peak-procedure and found that peak times shifted later.…”
Section: What Sets the Speed? A Key Direction For Future Neural Work ...mentioning
confidence: 99%
“…Consistent with this, disorders that preferentially disrupt MD-PFC communication, such as Schizophrenia, also disrupt timing (Ward et al, 2012 ; Singh et al, 2019 ). Furthermore, we recently provided initial causal data suggesting that selectively blocking communication between the MD and the prelimbic cortex—a rodent analog of the PFC—markedly disrupts timing (De Corte et al, 2021 ). Importantly, while monosynaptic MD-PFC projections are particularly relevant to Wang et al’s ( 2018 ) data, the MD is well positioned to modulate scaling in other areas, projecting heavily to the striatum, virtually all association cortices, and communicating with the hippocampus, presumably via reciprocal connections with parahippocampal structures (for excellent reviews see Saunders et al, 2005 ; Mitchell and Chakraborty, 2013 ; Pergola et al, 2018 ; Georgescu et al, 2020 ).…”
Section: What Sets the Speed? A Key Direction For Future Neural Work ...mentioning
confidence: 99%